Photoresist Removal Using H Radicals Generated by Iridium Hot-Wire Catalyst - Masashi Yamamoto; Shiro Nagaoka; Hironobu Umemoto; Keisuke Ohdaira; Takashi Nishiyama; Hideo Horibe (International Journal of Polymer Science)
We examined an environmentally friendly photoresist removal method using H radicals produced by decomposing hydrogen on a hot iridium catalyst. We examined the relationship between photoresist removal rate and its surface temperature using thin film interference and the removal properties using H radicals produced by the Ir catalyst. Decomposition behavior at polymer surface by radicals may be analyzed in further detail from the aspect of kinetics. Additionally, we investigated the oxygen addition effects on the removal rate. The photoresist removal rate increased with the oxygen additive amount and then decreased more gradually than in the case of using W filament. The increasing behavior was similar but there was a large difference between W and Ir catalyst in the decreasing behavior.